2016
DOI: 10.1093/infdis/jiw041
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Signatures Associated With Early Onset, Active Lesions and Late Cicatricial Events of Retinochoroidal Commitment in Infants With Congenital Toxoplasmosis

Abstract: These findings support the existence of a progressive immunological environment concomitant with the initial, apical, and cicatricial phases in the process of retinochoroidal lesion formation in infants with congenital toxoplasmosis that may be relevant in the establishment of stage-specific clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Data obtained from animal models support the notion that several fetal and neonatal pathological findings in humans can be related to both uncontrolled parasite replication and tissue necrosis, mediated by a robust T cell response (48)(49)(50). Likewise, Roberts et al (51) reported an association between the presence of T cells and increased ocular damage in retinal lesions from congenitally infected human fetuses and newborns (51), and more recently, a Brazilian group demonstrated an increased lymphocyte (CD4 + and CD8 + ) proliferation, as well as an increased production of the TNF-α in congenitally infected newborns, and particularly in those with early and active ocular lesions (52,53). Despite the previously mentioned protective effect of cytotoxic cells, it is known that this obligate intracellular parasite can use several mechanisms through which it evades not only cellular immunity, but also redirects the cell-mediated cytotoxicity to its advantage, favoring We suggest that transforming growth factor β (TGFβ) may have a pivotal role in controlling T. gondii vertical transmission, severity, and dissemination of the congenital infection.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained from animal models support the notion that several fetal and neonatal pathological findings in humans can be related to both uncontrolled parasite replication and tissue necrosis, mediated by a robust T cell response (48)(49)(50). Likewise, Roberts et al (51) reported an association between the presence of T cells and increased ocular damage in retinal lesions from congenitally infected human fetuses and newborns (51), and more recently, a Brazilian group demonstrated an increased lymphocyte (CD4 + and CD8 + ) proliferation, as well as an increased production of the TNF-α in congenitally infected newborns, and particularly in those with early and active ocular lesions (52,53). Despite the previously mentioned protective effect of cytotoxic cells, it is known that this obligate intracellular parasite can use several mechanisms through which it evades not only cellular immunity, but also redirects the cell-mediated cytotoxicity to its advantage, favoring We suggest that transforming growth factor β (TGFβ) may have a pivotal role in controlling T. gondii vertical transmission, severity, and dissemination of the congenital infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subsets of NK cells and CD8 + T cells act as biomarkers for cicatricial lesions of the eye8. It has also been demonstrated that NK cells show increased production of IFN-γ in patients with congenital ocular toxoplasmosis6. Furthermore, the high imunopathogenicity responsible for tissue damage and deterioration of ocular toxoplasmosis may be due to the presence of a potent inducer of inflammation, IL-1756, which is also produced by NK cells7.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that NK cells show increased production of IFN-γ in patients with congenital ocular toxoplasmosis6. Furthermore, the high imunopathogenicity responsible for tissue damage and deterioration of ocular toxoplasmosis may be due to the presence of a potent inducer of inflammation, IL-1756, which is also produced by NK cells7. On the other hand, ocular toxoplasmosis may be linked to autoimmunity14.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations